2014
DOI: 10.4103/2230-8598.127169
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum lipoprotein (a) in young patients with myocardial infarction

Abstract: Context: Indians are prone as a community to coronary artery disease (CAD) at a much younger age. CAD is affecting Indians 5-10 years earlier than other communities. Lipoprotein (a) (Lp (a)) is now recognized as an independent risk factor for CAD. It is a genetic risk factor. Aim: We evaluate the Lp (a) in young patients with myocardial infarction (MI). Settings and design: Study population consisted of 50 patients having MI and 50 control groups. Subjects and Methods: Fasting samples were collected from patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…High levels of TG (more than 150 mg/dl) were found in 37 % patients [mean ± SD (145.28 mg/dl ± 65.78)]. Our results were in agreement with that of Kamariya et al, [17] and Yadav and Bhagwat who reported increased TC, TG, LDL and decreased HDL levels in patients with ACS.…”
Section: % 33% 24%supporting
confidence: 92%
“…High levels of TG (more than 150 mg/dl) were found in 37 % patients [mean ± SD (145.28 mg/dl ± 65.78)]. Our results were in agreement with that of Kamariya et al, [17] and Yadav and Bhagwat who reported increased TC, TG, LDL and decreased HDL levels in patients with ACS.…”
Section: % 33% 24%supporting
confidence: 92%
“…In our study, patients admitted with CAD showed a significant increase in TG attributable to the ongoing inflammatory process, hepatic synthesis and lipolysis at the time of illness. In a study conducted by Kamariya et al, 13 showed high levels of TG (>150 mg/dl) in 63(33%). However, Siniawski et al, 12 in reported altogether different results showing nonsignificant changes in TG levels.…”
Section: Discussionmentioning
confidence: 90%
“…65, No. 1 (2022) lipoprotein (VLDL) receptors can bind to and mediate the catabolism of Lp (a) by endocytosis, leading to its degradation within lysosomes, leading to a cellular accumulation of lipids within macrophages [13,14].…”
Section: Fetuin-a (Human Fetuin-a or Alpha-2 Heremansmentioning
confidence: 99%